Corneal Diseases in Cats: A Retrospective Study of 477 Cases (2015-2020) - Demir, A; Sensoy, S (Journal of the Hellenic Veterinary Medical Society, 2023)
Corneal diseases are common in cats. If not diagnosed and treated in time, they can cause vision loss or even eye loss.This retrospective study aimed to introduce corneal disorders in cats, briefly explaining the therapeutic management of these disorders, and exploring the possibility of breed, age, and sex predisposition. In the study, a total of 477 cats, referred to the clinics of Istanbul University-Cerrahpasa, Faculty of Veterinary Medicine, and Department of Surgery between 2015-2020 with ophthalmological complaints and diagnosed with and treated for corneal disorders, were retrospectively evaluated. The most commonly encountered corneal disease was corneal ulcers (n=208, 43.60%), followed in descending order by corneal sequestrum (n=71, 14.8%), and corneal opacities (n=57, 11.9%) due to infection-associated symblepharon. Overall prevalence rates of ulcerative keratitis and non-ulcerative keratitis were 59.6% and 35.9%, respectively, in the study’s entire cat population. The congenital corneal diseases, such as persistent pupillary membrane (PPM) and corneal opacity due to endothelial dystrophy and acquired corneal disorders, such as corneal degeneration, scarring, and endothelial degeneration, were less frequently monitored conditions. In this study, it was seen that some corneal diseases in cats are more common in cats of certain breeds and ages, and corneal diseases are diseases that can be treated with early diagnosis. It has been noted that certain diseases are of infectious origin and are more likely to be treatable conditions.